2016
DOI: 10.1007/s11199-016-0646-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Essentialism in Children and Parents: Implications for the Development of Gender Stereotyping and Gender-Typed Preferences

Abstract: Psychological essentialism is a set of lay beliefs about categories, according to which certain categories are seen as natural and arising from an inborn, causal force or Bessence.Ŝ ocial categories, including gender, are often essentialized by both adults and children. The current study examines how gender essentialism relates to other gender-relevant beliefs and preferences, in both a child sample (5-to 7-year-olds) and an adult sample (the children's parents). Children's and parents' essentialism predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 58 publications
0
51
0
2
Order By: Relevance
“…Moreover, such training focuses largely on the biasing effects of descriptive aspects of gender stereotypes on evaluations, and thus will largely fail to address the negatively charged moral emotions evoked by agentic women (see [ 51 ]). Our findings provide preliminary evidence that a focus on challenging inaccurate GE beliefs, which may contribute to gender prescriptions, could potentially be a valuable alternative to unconscious bias training programs (see also [ 21 ]).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, such training focuses largely on the biasing effects of descriptive aspects of gender stereotypes on evaluations, and thus will largely fail to address the negatively charged moral emotions evoked by agentic women (see [ 51 ]). Our findings provide preliminary evidence that a focus on challenging inaccurate GE beliefs, which may contribute to gender prescriptions, could potentially be a valuable alternative to unconscious bias training programs (see also [ 21 ]).…”
Section: Discussionmentioning
confidence: 76%
“…More recently, Tinsley, Howell, and Amanatullah [ 20 ] found that greater endorsement of what they termed gender determinism (defined as “the strength of an individual´s belief that gender is a foundational force dictating a person´s characteristics”, p. 38) was associated with greater preference for a male primary breadwinner, as well as with work-family career tradeoffs that reinforce the gender wage gap. It has also been found that parents with stronger gender essentialist beliefs more strongly endorse gender prescriptions regarding appropriate jobs and activities for males and females, although this relation was not seen among their children [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using occupational presumptions about men and women, Experiment 1 showed how stereotypes influence decision-making. Of course, stereotypic beliefs about the sexes extend well beyond expectations concerning the professions that men and women are likely to occupy (Kite, Deaux, & Haines, 2008;Wood & Eagly, 2010), touching upon the characteristics they are likely to possess, the behaviors they are likely to enact, and the settings in which they are likely to be encountered (Haines, Deaux, & Lofaro, 2016;Heilman, 2012;Meyer & Gelman, 2016;Wood & Eagly, 2010). Accordingly, to establish the generality of the effects observed in Experiment 1, in our next studyagain in a face-label classification taskwe paired faces with personality characteristics that either confirmed or disconfirmed prevailing societal beliefs about the sexes (Wood & Eagly, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Boundaries between categories are treated as discontinuous and objectively correct, and category membership itself is viewed as immutable (24,(86)(87)(88)(89). Category members are thought to have innate potential that resists environmental influences (90)(91)(92). Internal bodily organs are thought to have the power to modify the recipient's behavior (93,94).…”
Section: Two Presuppositions: Norms and Essencesmentioning
confidence: 99%